EDUKACJA STUDENTA MINIMALNEGO: PRAKTYCZNA APLIKACJA TRYCHOTOMICZNEGO MODELU MAKSYMALNO-OPTYMALNO-MINIMALNEGO - Bogusławska-Tafelska, Marta (Acta Neophilologica, 2007)
The paper explores some aspects of the minimal student education. What attracts one’s attention are: the dyad encompassing the academic teacher and the minimal student; and the triad encompassing the academic teacher, the minimal student and the educational institution. The hypothesis orchestrating this study, preliminary as it is, contains the assumption that the disturbs both relations, bringing about the violation of the educational process. As a result, the methodological verification of the teaching procedures, as well as the psycholinguistic awareness raising process, have to be introduced if the minimal student education is to be continued.